Edukasi Hukum Berkeadilan Gender sebagai Upaya Pencegahan Kekerasan terhadap Perempuan bagi Pengurus ‘Aisyiyah di Medan - Atikah Rahmi; Ummi Salamah; Nalil Khairiah (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
Violence against women is very disturbing and causes injustice to the victims. Women are often victims of violence, because they are seen as weak and unable to fight the perpetrators. One of the causes of violence against women is gender inequality which creates unequal power relations between men and women. Unfortunately, this condition is often not realized by women because of the wrong understanding of what is considered as nature, which is gender. For this reason, it is necessary to educate the public, so that women no longer experience subordination which makes them vulnerable to becoming victims. Thus, violence against women can be minimized. Through the Muhammadiyah Development Partnership Program (PKPM), training is packaged that can educate MHH 'Aisyiyah administrators’ representatives from branches throughout the city of Medan to better understand gender and violence against women. The method used in this community service activity is training which begins with orientation and pre-test to the participants. The activity ended with a post-test. The post-test results showed an increase in participants' understanding of gender, forms of gender inequality, as well as knowledge about violence against women and efforts to prevent and deal with it.